Degenerations of democracy - Calhoun, Craig J., 1952- (Harvard University Press, 2022)
"Three leading thinkers analyze the erosion of democracy's social foundations and call for a movement to reduce inequality, strengthen inclusive solidarity, empower citizens, and reclaim pursuit of the public good"--